2010
DOI: 10.1038/onc.2010.301
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y and its Y2 receptor: potential targets in neuroblastoma therapy

Abstract: Neuroblastomas are pediatric tumors which develop from sympathetic precursors and express neuronal proteins, such as neuropeptide Y (NPY). NPY is a sympathetic neurotransmitter acting via multiple receptors (Y1-Y5R). Both NPY and Y2Rs are commonly expressed in neuroblastoma cell lines and tissues. The peptide secreted from neuroblastomas stimulates tumor cell proliferation and angiogenesis. Since both processes are Y2R-mediated, the goal of this study was to assess Y2R as a potential therapeutic target for neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(113 citation statements)
references
References 38 publications
9
104
0
Order By: Relevance
“…5) (Kitlinska et al, 2005). More importantly, blocking the NPY/Y2R mitogenic signaling reduces basal levels of p44/42 MAPK activity in neuroblastoma cells and significantly inhibits their proliferation (Lu et al, 2010). This effect is associated with an increase in neuroblastoma cell apoptosis mediated by the Bim pathway, known to be activated upon growth factor withdrawal (Lu et al, 2010).…”
Section: Neuropeptide Y -Neuronal Marker or Growth Factor?mentioning
confidence: 99%
“…5) (Kitlinska et al, 2005). More importantly, blocking the NPY/Y2R mitogenic signaling reduces basal levels of p44/42 MAPK activity in neuroblastoma cells and significantly inhibits their proliferation (Lu et al, 2010). This effect is associated with an increase in neuroblastoma cell apoptosis mediated by the Bim pathway, known to be activated upon growth factor withdrawal (Lu et al, 2010).…”
Section: Neuropeptide Y -Neuronal Marker or Growth Factor?mentioning
confidence: 99%
“…NPY induces NB tumour growth and angiogenesis (Kitlinska et al 2005). NY2R is the most common NPY receptor expressed in NB cells and blocking the binding of NPY to NY2R has been proposed as an approach to inhibit NB growth (Lu et al 2010). It has been shown that blocking NY2R results in a decrease in NB proliferation rate, it induces apoptosis and in vivo studies show an impairment of the tumour vascularisation as well (Lu et al 2010).…”
Section: S Verissimo Et Al: Novel Neuroblastoma Targetsmentioning
confidence: 99%
“…We recently proposed to target doublecortin-like kinase (DCLK1) to inhibit NB proliferation and induce apoptosis (Verissimo et al 2010). In addition, neuropeptide Y (NPY) and its Y2 receptor (NY2R) were selected as examples of antiangiogenesis targets (Lu et al 2010). The high expression levels of the sympathetic neurotransmitter NPY correlates with MYCN amplification and with poor clinic outcome (Dötsch et al 1998).…”
Section: Proposed Molecular Targets Not Yet Explored In the Clinicmentioning
confidence: 99%
See 2 more Smart Citations